Climate Impact Platform Area Webinar Series - Webinar 2: Loss and Damage—Understanding its past, present, and future - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
The planet has already warmed by approximately 1.1°C due to human-induced climate change, affecting every region and impacting millions with higher temperatures, less predictable rainfall, rising seas, and fiercer storms. The agrifood sector, which supports 3.83 billion livelihoods, is especially vulnerable due to its dependence on weather.